IMPLEMENTASI KEBIJAKAN PENATAAN KAWASAN PASAR TRADISIONAL KOTA DUMAI STUDI KASUS DI PASAR BUNDA SRI MERSING TAHUN 2021 – 2022 - Nazelia, Marsella; Marta, Auradian (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
This research is based on the large number of traders selling in front of the Bunda Sri Mersing Traditional Market area, Dumai city, precisely on Jalan Sultan Hasanudin, which causes traffic disruption and often causes traffic jams. As stated in the Dumai City Regional Regulation Number 8 of 2017 concerning the Arrangement of Traditional Market Areas, which in this Regional Regulation, the Mayor through the Trade Service makes efforts to organize the Traditional Market area in Chapter III Article 4 paragraph 1. This research aims to explain the Implementation of the Regional Arrangement Policy Bunda Sri Mersing Traditional Market, Dumai City. In this research, the author uses a qualitative research method, which requires setting boundaries in the research based on the focus that arises as a problem in the research as well as preparing a design that is continuously adapted to the reality in the field. This research is based on the Varn Meter and Varn Horn theory. The results of the research show that the implementation of the policy for structuring the Bunda Sri Mersing Traditional Market area in Dumai City can be said to have not been optimal. Due to several factors, namely, insufficient budget resources, relationships between organizations that have not been well established, and economic and social conditions where there are still many problems in the field which influence the implementation of the policy for structuring the Bunda Sri Mersing Traditional Market area. Keywords: Implementation, Policy, Traditional Market Structuring